The Role Of The Headmaster In Improving The Quality Of Education At Taska Al Fikh Orchard, Ayer Tawar, Malaysia - Umara, Fahdisya Nuzly (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The purpose of this study is to explore the role of school principals in enhancinf the quality of education at Taska Al-Fikh Orchard, Ayer Tawar, Malaysia. This research aims to understand how the leadership of school prinncipals can influence the learning environment and educational outcomes for early childhood education. The methodology used in this study is a descriptive qualitative approach, which involves observation, in-depth interviews, and documentation to gather data from various sources, including teachers, parents, and school administrators. The findings indicate that school principals play a crucial role in creating a positive school culture, implementing appropriate Standard Operating Procedures (SOPs), and facilitating training for teachers. Support from parents and the community has also proven to be a key factor in improving educational quality. However, the institution faces various challenges, such as limited resources and pedagogical skills among teachers, as well as the need for additional support for school principals through training and professional development. The main conclusion of this research is that effective leadership and collaboration with all stakeholders are essential in creating a quality learning environment. This is important for addressing existing challenges and ensuring that children receive quality education according to their potential. The study highlights the need for futher development in leadership training for school principals to achieve better educational outcomes.